Exploration of electro-optic modulators - Teng, Jin Siang. (2009)
Electro-optic modulators (EOM) are the key elements in optical fiber telecommunication systems, radio over fiber system, microwave photonics filters, etc. Through the EOMs, the electrical signals can be modulated onto the optical carrier thus the signals can be transmitted through the optical fiber. The modulation may be imposed on the phase, frequency, amplitude or intensity. Modulation bandwidths extending into the gigahertz range are possible. In this project, it will give a thorough overview of the optical fiber technology and Electro-Optic Modulators in a transmission link. Besides that, simulation of the EOMs is also useful to model the behavior of the EOMs. A Graphic User Interface using MATLAB was developed. Optical phase modulation and optical intensity modulation were developed in this GUI. The experimental measurement on real devices helps to observe the practical behavior of the external modulator.